2020
DOI: 10.1186/s12887-020-02076-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical audit in the pediatric primary care office and overweight prevention in toddlers

Abstract: Background: Clinical audit is a process by which physicians or other health care professionals perform a regular and systematic review of their clinical practice and amend it, when necessary. An internal audit allows to review the activities carried out by professionals, in order to assess the appropriateness, effectiveness, efficiency and safety of the services provided. Aim of this study was to apply the process of clinical audit to the obesity/overweight care in toddlers. After the correction of the nutriti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(19 reference statements)
0
1
0
1
Order By: Relevance
“…No início da vida de uma criança, os fatores nutricionais influenciam mais no ganho de peso do que os fatores ambientais, sendo indispensável a atuação dos profissionais da saúde em fornecer orientações corretas na introdução alimentar e alertar sobre os riscos no desenvolvimento da obesidade infantil. No sul da Itália, existe uma prevalência de sobrepeso e obesidade infantil, sendo a mais alta do país, o que salienta a necessidade de ter medidas educativas e uma reavaliação cuidadosa das recomendações dadas aos familiares durante esse momento de introdução alimentar 15 .…”
Section: Discussionunclassified
“…No início da vida de uma criança, os fatores nutricionais influenciam mais no ganho de peso do que os fatores ambientais, sendo indispensável a atuação dos profissionais da saúde em fornecer orientações corretas na introdução alimentar e alertar sobre os riscos no desenvolvimento da obesidade infantil. No sul da Itália, existe uma prevalência de sobrepeso e obesidade infantil, sendo a mais alta do país, o que salienta a necessidade de ter medidas educativas e uma reavaliação cuidadosa das recomendações dadas aos familiares durante esse momento de introdução alimentar 15 .…”
Section: Discussionunclassified
“…Allene's [ 6 ] goal was to evaluate whether the World Health Organization's (WHO) surgical safety checklist was correctly completed. According to this study, checklists can increase surgical safety, but how well they are implemented will determine how effective they are.…”
Section: Introductionmentioning
confidence: 99%
“…According to this study, checklists can increase surgical safety, but how well they are implemented will determine how effective they are. The checklist's overall completeness during the sign-in, time-out, and sign-out periods was good [ 6 ]. The clinical audit of the WHO surgical safety checklist served as the basis for the recommendations made in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a systematic review of systematic reviews on the effects of nutritional exposure or interventions in children under 3 years, underscored the promising effect of lowering the protein intake of infant formula or complementary food on the risk of later OW/OB [13]. Indeed, a previous study conducted by primary care pediatricians demonstrated that simple but speci c dietary advices, focused on the choice and amount of food with low protein content and sugar, were associated to a reduction of the frequency of OW and OB in toddlers living in an Italian region with high prevalence of OW/OB [14].…”
Section: Introductionmentioning
confidence: 99%